Enhanced microwave absorbing performance of Ni-containing SiCN ceramics by constructing multiple interfaces and in-situ generating MWCNTs. Issue 22 (15th November 2022) - Liu, Maoyun; Lu, Junbin; Gong, Hongyu; Sheng, Mingming; Jing, Jie; Sun, Shan; Wang, Guantong; Miao, Yalan
Abstract: Ni-containing SiCN ceramics as microwave absorbing materials were successfully synthesized by facile polymer derived ceramics (PDCs) route using nickel acetates tetrahydrate (Ni(Ac)2 ·4H2 O) and polysilazane (PSZ) as raw materials and pyrolyzing at 1200 °C. After introducing Ni(Ac)2 ·4H2 O, a large number of multi-walled carbon nanotubes (MWCNTs) were in-situ formed in Ni-containing SiCN ceramics. Besides, some crystalline phases, such as Si3 N4, β-SiC, Ni2 Si, Si2 N2 O and turbostratic carbon, were observed. The 3D conductive network constructed by the MWCNTs and multiple heterogeneous interfaces formed by various phases were generated in SiCN matrix, which enhanced the electromagnetic wave (EMW) absorbing performance of Ni-containing SiCN ceramics. The morphology and electromagnetic parameters of Ni-containing SiCN ceramics could be effectively regulated by changing the addition content of Ni(Ac)2 ·4H2 O. The Ni-containing SiCN ceramics with the Ni(Ac)2 ·4H2 O addition content of 15 wt% presented the best electromagnetic wave absorption property. Its minimum reflection loss (RLmin ) reached −60.71 dB at 9.44 GHz with the thickness of 2.20 mm and effective absorption bandwidth (EAB) broadened to 4.36 GHz (13.64–18 GHz) at 1.38 mm. The excellent properties should be mainly attributed to the synergistic effects of good impendence matching, conduction loss and polarization relaxation loss.